Problem Based Learning to Improve HOTS of High School Students - LUCIANA DWI NOMA; BASKORO ADI PRAYITNO; SUWARNO SUWARNO (Bioedukasi: Jurnal Pendidikan Biologi, 2016)
This research aimed to improve the high-order thinking ability of students by applying PBL model in Environment Pollution of 10th MIA 3 graders of SMA Negeri 2 Sukoharjo. This study was a classroom action research followed the Kemmis and Mc. Taggart’s, and conducted in two cycles, from April to May 2016. Each cycle consisted of 4 stages: planning, acting, observing, and reflecting. The participants were 31 students (18 female and 13 male students) of 10th MIA 3 graders of SMA Negeri 2 Sukoharjo. Data was obtained using essay test on the high-order thinking ability, interview, observation sheet on the implementation of PBL syntax, observation sheet on affective and psychomotor aspects of students. Essay test of high-order thinking ability includes: analyzing (C4), evaluating (C5), and creating (C6) based on Bloom’s revised taxonomy. Data analysis was descriptively. The target of research was the improvement of students’ high-order thinking ability in every aspect more than 23% from based line to the end of research cycle. The result shows that the PBL model in environment pollution material is able to improve the high-order thinking ability of students by ≥23% from based line to the end of research cycle. The increase of percentage gain in each aspect of high-order thinking ability from pre-cycle to cycle II was as follows: 1) the analyzing aspect increased by 25.16%, 2) the evaluating aspect increased by 26.66%, and 3) the creating aspect increased by 23.95%.